A REVIEW OF CURRENT BOVINE OBSTETRICAL PRACTICES - GHUMAN, S P S; SINGH, N (The Indian Journal of Animal Reproduction, 2022)
The dairy animal population especially buffalo suffers from various obstetrical problems, the solution for someof these have been devised and are in process for the others. There is need to understand management factorsassociated with uterine torsion in buffaloes, the physiological and cardiovascular impact of dystocia. This willhelp in timely resuscitation of dystocia-affected dam through the use of tranquilizers, glucocorticoids plus antioxidantsand crystalloid plus colloid based fluid therapy. Huge success has been achieved in cervical massage orintracervical treatment for dilatation of incompletely dilated cervix as well as timely and appropriate handling of anobstetrical case by understanding the importance of time factor. The use of uterine lubricants improves successrate. Fetotomy should be used as preferred obstetrical procedure by making the availability of an appropriateFetotomy kit and the knowledge of ‘Strength-Stamina-Skill’ for carrying out fetotomy procedures.
Keywords: Buffalo; Doppler; Fetotomy; Obstetrics; Uterine torsion